The Potential Impact of Saharan Dust and Polluted Aerosols on Microbial Populations in the East Mediterranean Sea, an Overview of a Mesocosm Experimental Approach - Herut, Barak; Rahav, Eyal; Tsagaraki, Tatiana M.; Giannakourou, Antonia; Tsiola, Anastasia; Psarra, Stella; Lagaria, Anna; Papageorgiou, Nafsika; Mihalopoulos, Nikos; Theodosi, Christina N.; Violaki, Kalliopi; Stathopoulou, Eleni; et al. (Frontiers in Marine Science, 2016)
Recent estimates of nutrient budgets for the Eastern Mediterranean Sea (EMS) indicate that atmospheric aerosols play a significant role as suppliers of macro- and micro- nutrients to its Low Nutrient Low Chlorophyll water. Here we present the first mesocosm experimental study that examines the overall response of the oligotrophic EMS surface mixed layer (Cretan Sea, May 2012) to two different types of natural aerosol additions, “pure” Saharan dust (SD, 1.6 mg l-1) and mixed aerosols (A - polluted and desert origin, 1 mg l-1). We describe the rationale, the experimental set-up, the chemical characteristics of the ambient water and aerosols and the relative maximal biological impacts that resulted from the added aerosols. The two treatments, run in triplicates (3 m3 each), were compared to control-unamended runs. Leaching of approximately 2.1-2.8 and 2.2-3.7 nmol PO4 and 20-26 and 53-55 nmol NOx was measured per each milligram of SD and A, respectively, representing an addition of approximately 30% of the ambient phosphate concentrations. The nitrate/phosphate ratios added in the A treatment were twice than those added in the SD treatment. Both types of dry aerosols triggered a positive change (25-600% normalized per 1 mg l-1 addition) in most of the rate and state variables that were measured: bacterial abundance (BA), bacterial production (BP), Synechococcus (Syn) abundance, chlorophyll-a (chl-a), primary production (PP) and dinitrogen fixation (N2-fix), with relative changes among them following the sequence BP>PP≈N2-fix>chl-a≈BA≈Syn. Our results show that the ‘polluted’ aerosols triggered a relatively larger biological change compared to the SD amendments (per a similar amount of mass addition), especially regarding BP and PP. We speculate that despite the co-limitation of P and N in the EMS, the additional N released by the A treatment may have triggered the relatively larger response in most of the rate and state variables as compared to SD. An implication of our study is that a warmer atmosphere in the future may increase dust emissions and influence the intensity and length of the already well stratified water column in the EMS and hence the impact of the aerosols as a significant external source of new nutrients.